De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Fu, Lili (Physiol Mol Biol Plants, 2019)
Lemna gibba is a species of duckweed showing great potential in bioenergy production and wastewater treatment. However, the relevant transcriptomic and genomic resources are very limited for this species, which dramatically hinders its genetic diversity and genome mapping researches. In this work, ~ 233.5 million clean reads were generated from L. gibba by Illumina paired-end sequencing, and subsequently they were de novo assembled into 131,870 unigenes, of which 61,622 were annotated and 43,319 were expressed with Fragments Per Kilobase of transcript per Million fragments mapped (FPKM) > 5. In total, 19,297 simple sequence repeats (SSRs) were identified from 15,261 SSR-containing unigenes. Dinucleotide (78.4%) were the most abundant SSRs, followed by tri- (14.9%), tetra- (4.1%), and penta-nucleotides (1.5%). The top three motifs were AG/CT (69.9%), AC/GT (6.5%), and ATC/ATG (4.9%). Further analysis revealed that the presence of SSR motif was independent of the expression level for a given gene. Based on the sequence of these SSR-containing unigenes, a total of 10,292 SSR markers were developed, of which only 2671 were further retained after removing those derived from unannotated or extra-low expressed (e.g., FPKM ≤ 5) unigenes. Finally, a subset of 70 SSR markers was randomly selected and examined in nine diverse L. gibba genotypes for the PCR amplification and polymorphism, as well as in other duckweed species for the inter-specifically amplifiability. This work is the first report on the transcriptome-based large-scale SSR markers development and analysis in L. gibba. The transcriptome generated and the SSR markers developed in this work will provide a valuable resource for genetic diversity assessment in L. gibba and also for species relationship investigation in Lemnaceae family. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12298-019-00726-9) contains supplementary material, which is available to authorized users.